Hubungan Partisipasi Keluarga dengan Kosakata pada Anak dengan Permasalahan Komunikasi - Fitria Rahmawati, Annisa; Triantoro Aji Pratomo, Hafidz; Nugroho, Setyadi (Jurnal Terapi Wicara dan Bahasa, 2024)
Background: The role of parents is very important for children, this is because dealing with children with communication problems parents need to know special skills to guide children. Vocabulary is very important and necessary in communicating verbally with others and also the mastery of vocabulary owned by a person also affects the ability to understand something. Objectives: This study aims to provide an overview of the relationship between family participation and vocabulary in children with communication problems in Sukoharjo District. Methods: This study is a quantitative study with a cross sectional study design, involving 30 parent respondents who have children with communication problems at the Sukoharjo Regency Language and Speech Learning Clinic. The data in this study were analysed univariately and bivariately. The statistical test used is using Spearman's Rank test. Results: The results of the analysis test showed =0.001 (Ha accepted) with a correlation coefficient of r=0.566 which shows the relationship between the two variables in the strong category with a positive direction. Conclusion: Based on the results of data analysis, it can be concluded that there is a significant relationship between family participation and vocabulary and further research needs to be done on the relationship between family participation and vocabulary. Keywords : Communication, Family, Language, Participation, Vocabulary